Refugees' perceptions regarding HIV and AIDS in Ba-Phalaborwa Municipality in Limpopo Province - Elizabeth Nkwinika; Lunic B. Khoza; Rachel T. Lebese; Hildah N. Shilubane (AOSIS, 2014)
Background: Human Immunodeficiency Virus and Acquired Immune Deficiency Syndrome (HIV and AIDS) remain a serious threat to population health and economic well-being of individuals in conflict societies. Sub-Saharan Africa (SSA) is overwhelmingly affected by HIV and is the region with the highest number of armed conflicts worldwide. Aim: The research aimed at exploring and describing the perceptions of the refugees at Humulani Village in Ba-Phalaborwa municipality, Limpopo province, about HIV and AIDS. Objectives: The objectives included determining the gender perceptions about HIV and AIDS and also providing recommendations for ways to increase the refugees understanding of this disease. Methods: The approach used for the research was quantitative. The target population of the study was all the refugees at Humulani Village. The sample comprised both men (n = 78) and women (n = 122) who participated by completing questionnaires. The sample of the refugees consisted of different ethnic groups from Mozambique, Nigeria, Ghana and Zimbabwe. The questionnaire consisted of two sections, section A contained the biographic data and section B interrogated the refugees' knowledge of HIV. Results: The findings of the study revealed that the participants had low levels of knowledge regarding HIV which could be attributed to their believing the myths about HIV and AIDS. Conclusion: The HIV-infected refugee population in Limpopo may continue to grow unless the unique needs of the refugees, such as strengthening the reproductive health services, maternal and child care and family planning, improving the educational and socio-economic status, are not addressed. Agtergrond: Menslike immuniteitsgebrekvirus (MIV) en verworwe immuniteitsgebrek-sindroom (vigs) bly 'n ernstige bedreiging vir die gesondheid van die bevolking, asook die ekonomiese welstand van individue in konflik-samelewings. Sub-Sahara Afrika (SSA) word oorweldigend deur MIV geraak en is die streek met die hoogste aantal gewapende konflikte wêreldwyd. Doelwitte: Die navorsing het ten doel gehad om vlugtelinge te Humulani dorpie in Ba-Phalaborwa munisipaliteit, Limpopo provinsie, se persepsies oor MIV en vigs te ondersoek en beskryf. Die doelwitte het die bepaling van geslagspersepsies oor MIV en vigs ingesluit, asook om aanbevelings te bied vir maniere om die vlugtelinge 'n beter begrip van MIV en vigs te gee. Metode: 'n Kwantitatiewe benadering tot hierdie navorsing is gevolg. Die teikenpopulasie van die studie was al die vlugtelinge te Humulani dorpie. Die steekproef het uit beide manlike (n = 78) en vroulike (n = 122) deelnemers bestaan wat vraelyste voltooi het. Die steekproef vlugtelinge was van verskillende etniese groepe afkomstig: Mosambiek, Nigerië, Ghana en Zimbabwe. Die vraelys het twee afdelings gehad: Afdeling A het die biografiese data bevat en Afdeling B het die vlugtelinge se kennis van MIV ondersoek. Resultate: Die bevindinge van die studie het onthul dat die deelnemers oor lae kennisvlakke rakende MIV beskik - dit kan toegeskryf word aan hul geloof in die mites aangaande MIV en vigs. Gevolgtrekking: Die populasie van MIV-besmette vlugtelinge in Limpopo mag steeds groei indien daar nie aandag geskenk word aan die unieke behoeftes van die vlugtelinge nie, soos die versterking van voortplantingsgesondheidsdienste, gesinsbeplanning, en moeder- en kindersorg, asook die verbetering van hul opvoedkundige en sosio-ekonomiese welstand.